Anthropocene: An Analytical Reading of Human Domination on Earth in Contemporary Literature Case Study: H.G Wells’s The Time Machine (1895) - Bengana,Nadia; Choucha,Amina; Hocine,Aicha (University of Ammar Theledji -Laghouat, 2020)
The quest for meaning and finding the purpose of existence are two of the most mysterious tasks for human beings. As time passes by, the puzzle becomes even more complicated and more difficult to be answered. Accordingly, humanity‘s constant search for dominance over the planet to grasp power has ultimately contributed to the emergence of the Anthropocene‘s novel. In this light, the aim of this dissertation was to examine the significance of introducing the effects of human actions on the planetary and to explore the relationship between the Anthropocene and humanity‘s fate in the novel of The Time Machine (1895) written by H.G Wells. To achieve this aim, the researchers adopted the descriptive and analytical approaches. This dissertation, then, questions the reason behind the emergence of the Anthropocene in literature. Therefore, it hypothesizes that literature is no longer distinct from the world conditions in which the Anthropocene challenges us to think beyond the human scale, to imagine planetary forces, histories and spaces in the face of which humans shrink into insignificance. This study ultimately concluded that humans were a direct force over the planet and the reason behind the emergence of the Anthropocene in literature. In addition, if they perceived their exploitation of the planet they would ultimately be the end of their existence and the existence of their own planet. As a result, a number of solutions were suggested that may put an end to this inevitable fate of humanity and earth